Emergy evaluation of biogas production system in China from perspective of collection radius. (15th February 2023) - Sun, Yufeng; Yang, Bin; Wang, Yapeng; Zheng, Zipeng; Wang, Jinwei; Yue, Yaping; Mu, Wenlong; Xu, Guangyin; Jilai Ying
Abstract: Biogas production has become one of the main renewable energy utilization modes in Chinese rural areas. In this study, emergy theory was employed to assess the ecological sustainability of biogas production system based on the case of Weilai energy company. Emergy radius formulas derived from biogas production characteristics were constructed to illustrate the relationship between the degree of system development and biomass supply distance. The calculated emergy results showed that the biogas production system required an average of 1.98 E+14sej emergy inputs in the process of utilizing one-ton agricultural waste. And the emergy indicators implied that the system had a low degree of social resource input and environmental loading, indicating that the system could keep high output efficiency and ecological sustainability. The biomass recycling distance (9.93 km) which was calculated from emergy radius demonstrated better ecological performance and higher waste utilization degree than that of economic recycling distance (7.57 km). Biomass recycling distance based on emergy theory would provide a comprehensive understanding for the biogas production development. Highlights: An efficient biogas production system for agricultural waste recycling. Comprehensive evaluation of the biogas production system with emergy theory. Emergy radius formulas of biogas production were constructed. Decision method of feedstock supply distance of biogas production based on emergy analysis. Higher feedstock supply distance (9.93 km) obtained by energy index radius than that of the economic radius (7.57 km).